1919
DOI: 10.1515/bchm2.1919.105.3-4.83
|View full text |Cite
|
Sign up to set email alerts
|

Verstärkung der Katalasewirkung in Hefezellen.

Abstract: Mit 2 Figuren im Text. (Aus dem biochemischen Laboratorium der Universität Stockholm.) (Der Redaktion zugegangen am 15. März 1919.) Älmliche Vorbehandlungen, wie diejenigen, welche nach den Untersuchungen des hiesigen Laboratoriums*) zu einer Vermehrung der Invertasewirkung in der Hefe führen, steigern gleichzeitig auch andere Enzymwirkungen 2). Dies trifft allerdings nicht für-sämtliche Hefenenzyme zu, und bei denjenigen Enzymwirkungen, welche erhöht werden, ist, wie• schon betont wurde, die Zunahme prozentis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1921
1921
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…3). A similar phenomenon was observed for catalase activity in distiller's yeast (7). Aryl sulfatase is quite stable at elevated temperatures; however, after the first 5 min of heat treatment, aryl sulfatase activity decreased at a rate parallel to the loss of activity in conidia whose permeability barrier was previously destroyed with chloroform.…”
Section: Methodssupporting
confidence: 72%
“…3). A similar phenomenon was observed for catalase activity in distiller's yeast (7). Aryl sulfatase is quite stable at elevated temperatures; however, after the first 5 min of heat treatment, aryl sulfatase activity decreased at a rate parallel to the loss of activity in conidia whose permeability barrier was previously destroyed with chloroform.…”
Section: Methodssupporting
confidence: 72%
“…The L forms lyse to a large extent when transferred to dilute buffers, whereas normal bacteria are highly resistant to osmotic forces. This could explain the higher catalase activity of the L forms, since it is known that a degradation of the structure of microbial cells enhances their catalase activity (Euler and Blix, 1919; Herbert and Pinsent, 1948;Preiss, 1959). The low catalase activity of one of the L forms, L 9, may also be explained by lytic effects.…”
Section: Discussionmentioning
confidence: 97%
“…Pure catalase has a turnover number of about 107 molecules per min per molecule of catalase (Sumner and Somers, 1947;Herbert and Pinsent, 1948). However, catalase molecules inside intact cells seem to split H202 about ten times slower (Euler and Blix, 1919;Herbert and Pinsent, 1948), and are thus characterized by a turnover number of about 106. The average diameter of PPLO cells is approximately 0.4 ,u (Bartmann and Hopken, 1955;Weibull and Lundin, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…They are of the opinion that this may result from the destruction of harmful soil organisms or be a direct physicalchemical effect. Euler and Blix (1919) found that low concentrations of certain protoplasmic poisons would considerably accelerate the catalase activity of yeast cells.…”
Section: Resultsmentioning
confidence: 99%